DIGITAL MARKETING AND THE IMPACT ON BRAND AWARENESS ANSWERING THE ELUDING QUESTION OF CONSUMER BEHAVIOR IN AZERBAIJAN’S LUXURY SEGMENT - Ismayilzada, Orkhan (Global journal of Business and Integral Security, 2023)
The purpose of this study is to investigate the performance of luxury brands in Azerbaijan as a function of their digital marketing strategies. The study uses consumer behavior as a moderator for the relationship. The method applied as quantitative in nature by utilize binary logistic regression and chi-square tests in order to assess the potential relationships between the variables. It has been found that there is a significant correlation between digital marketing and consumer behavior elements, there is a significant impact between consumer behavior and brand awareness. The conclusion of the study is that while luxury brands can benefit from their digital strategies to improve awareness but it is difficult to positively impact attitudes of consumers in this segment in Azerbaijan and lastly, further recommendations and implications have been discussed in the study.